PEMBUATAN PEMANAS AIR MANDI DENGAN SUMBER ACCUMULATOR DAN MENGGUNAKAN SENSOR INFRA RED - ARVAN, Dean (2012)
To focus a clear direction and issues in order to achieve the purpose of this final course, it is desirable to limit the problem to be revealed. The author would limit the issues to be discussed. Making bath water heating system bersum berdari battery (accumulator) and uses infra red sensors. Rectifiers are used as a rectifier in the circuit chargerbattery which serves also as a battery charger when the battery is empty Inverter is used to have a power source of the battery (accumulator) An infrared sensor is a device that is capable of transmitting and receiving infrared waves. At the time the current flows from the AC source is connected to a step-down transformer. The transformer is used to lower the AC voltage is then converted into DC voltage for charging purposes accumulator or batteries. The voltage of the net - net amounted to PLN 220 volts down to a step-down transformer to 16 volts, because the voltage required for charging the batteries is DC voltage and the voltage of the transformer is still streamy AC voltage, the voltage of the transformer is rectified by the diode. At the time of filling can be seen with the lit LED lighting, LED lights light up while charging and LED lights when not filling out. At the time of the supply flow from PLN lost, the supply voltage of the battery will be converted DC voltage by a voltage inverter circuit for water heater requires AC voltage from the AC source. Heating bath water by using the source accumulator, it can still work if you are not using source of electricity, by using the inverter as a voltage converter DC to AC voltage on the accumulator to be used as a source for the heater. Inverter used is a series created by writer, producing 12 Volts, then use the step-up transformer, so the voltage produced by the inverter output to 220 volts, and has been used for 150 Watt serves as a water heater.